Efficacy and side effects of Blacksoap® as adjuvant therapy of scabies: a randomized control trial (Medical Journal of Indonesia, 2022)
BACKGROUND Blacksoap® is recognized as adjuvant therapy for scabies, but there has been no significant study on its effectiveness. This study aimed to compare the efficacy and safety between Blacksoap® and placebo on standard treatment for pruritus visual analog scale (VAS) and transepidermal water loss (TEWL) scores before and after receiving therapy. METHODS This single-blind randomized controlled trial was held in a boarding school in West Java in 2018. Subjects were recruited consecutively by random cluster sampling. Both groups received standard permethrin 5% cream therapy. The intervention group (n = 37) obtained Blacksoap®, while the control (n = 41) received baby soap. During the initial assessment, pruritus VAS and TEWL scores were taken. The cure rate, scores of pruritus VAS and TEWL, as well as side effects were assessed and compared during the first and fourth weeks. Data were analyzed using SPSS software version 20 (IBM Corp., USA) by a third party, mostly using non-parametric tests. RESULTS The cure rate of the intervention group was lower than the control in the first week with 75% versus 81% but higher in the fourth week with 97% versus 92%. There was no significant difference in the scores of pruritus VAS and TEWL, as well as side effects between the two groups. CONCLUSIONS The efficacy and safety of scabies treatment were similar between Blacksoap® and placebo adjunctive to standard treatment. Blacksoap®, on top of standard scabies treatment, might benefit patients by providing a higher cure rate in 4 weeks without any considerable adverse effects.